BPS multi-vortices in chiral perturbation theory - Vera Aldo (EPJ Web of Conferences)
We show that a BPS bound can be derived from chiral perturbation theory minimally coupled to electrodynamics at a finite isospin chemical potential. At a critical value of the isospin chemical potential, and for a fixed pressure value, a system of coupled first-order differential field equations can be derived for the gauge potential and the hadronic profile. This BPS system is solved by magnetic multi-vortices with quantized flux supported by a superconducting current. The topological charge density is related to the magnetic flux, but it is dressed by the hadronic profile. We discuss some of the main physical properties of this novel BPS bound. In particular, we show that a critical value for the magnetic field can be deduced.